REDEFINING OWNERSHIP: DIGITAL ASSETS, INTELLECTUAL PROPERTY, AND EMERGING TECHNOLOGIES - Sanek, Siti Khadijah Abdullah; Kamarudin, Irma; Kamarudin, Arina (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This article examines the evolving relationship between digital assets, intellectual property (IP), and emerging technologies, with a particular focus on legal implications under European Union (EU) law. Innovations such as digital assets, such as cryptocurrencies, non-fungible tokens (NFTs), and artificial intelligence (AI) generated works, are reshaping concepts of ownership and intellectual property (IP). The article adopts a threefold methodological approach. To assess the adequacy of current legal frameworks, a systematic review highlights key limitations in applying traditional property law to intangible assets like cryptocurrencies and NFTs. The second element analyses the effects of emerging technologies on IP rights and regulatory compliance through an interdisciplinary synthesis of recent research. Lastly, a comparative legal analysis draws on EU and international case studies to identify regulatory gaps and propose policy responses. The findings suggest that while digital assets promote innovation, their decentralised and intangible nature poses challenges to core legal concepts such as exclusivity, attribution, and enforceability. Despite progress in EU digital regulation, inconsistencies persist across jurisdictions. The article concludes that a more harmonised legal framework supported by clearer definitions, the integration of smart contracts, and effective cross-border dispute mechanisms is necessary to ensure that IP law remains effective in the digital economy.